National survey on current management of ovarian tumors in pediatric age group - Ahmed Elgendy; Sherif Shehata (SpringerOpen, 2018)
Aim of the study: To investigate the current management of ovarian tumors in children by the Egyptian pediatric surgical association (EPSA) consultants who are dealing with approximately 80% of these cases in our country. Methods: Following approval of EPSA executive board, an online questionnaire was sent via e-mails on EPSA online group mail to all registered consultants. Repeated reminders were sent biweekly for 6 weeks. Results: Responses were received from 82 consultants (response rate 82/111, 73.87%). Diagnosis: 74.39% of respondents indicated abdomino-pelvic mass as most common presenting symptom. Concerning imaging requested, US and CT were reported by 60.98%. AFP and HCG were requested by 84.15% as serum tumor markers. Surgery: Approximately 50% of respondents perform 1-3 cases per year. Diagnostic laparoscopy was done by 70.73%. Transverse abdominal incision was the commonest in use during surgeries (81.71%). Out of all respondents, 65.85% never encountered intraoperative complications, whereas the remaining 34.15% had different complications (mainly rupture and spillage). Minimally invasive surgery (MIS) was adopted by 53.66% in only benign looking tumors. A total of 69.51% perform ovarian sparing surgery (OSS) in benign masses whenever possible. Follow up: Benign tumors were the most common type observed by 86.59% of respondents. In benign lesions, 28.05% of surgeons never ask for follow up and the remaining 71.95% follow patients with different schedules. Conclusions: There is a paradigm shift toward MIS and OSS in the current practice of EPSA consultants. No actual standard protocol of management is present for ovarian tumors in Egypt and they still fall at the edge between many subspecialties. The results of this survey urge for establishment of uniform guidelines with international reference to be adopted in our nation, in addition to start a national prospective registration system for these tumors which is currently lacking in Egypt.